UPAYA MENINGKATKAN HASIL BELAJAR MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) (Penelitian Tindakan Kelas Pada Siswa Kelas V Sdn 3 Sindangratu Kecamatan Panggarangan Kabupaten Lebak Tahun 2021) - Tri Julyanto; Encep Andriana; Ratna Sari Dewi (PREDIKSI (PROFESI PENDIDIKAN INDONESIA), 2021)
The purpose of learning is to achieve of mastery of the material conveyed by teacher to students and the indicator of this achievement is to improve student learning out comes and improve the student learning result, especially in the learning process there is an active interaction between teachers and students. From the results of observation at SDN 3 Sindangratu, feed back from students in the learning process is not optimal and student learning result are low on theme 7, theme 8 and theme 9. Based on thes problems, improvement effort are proposed through the aplication of the STAD type cooperative learning model.The formulation of the problem in this researchis whether the aplicationof the STAD type cooperative learning model can improve student learning outcomes on theme 7, 8 and 9 in class V SDN 3 Sindangratu in the 2020/2021 school years. The aim of research is to describe the learning outcomes of the fifth grade students of SDN 3 Sindangratu for the 2020/2021 akademic year. This research is a classroom action research conducted at SDN 3 Sindangratu, Panggarangan District Lebak Regency, in class V the total student is 20. This research is designed in cycle. Each cycle consist of planning, implementation, observation, replection, and data analysis using the average. Based on student learning outcomes after using the STAD type cooperative learning model has in creased. This can be seen from the increase in the average value of student knowladge in cycle I is 66, in cycle II is 74.75 and in cycle III is 83.25, an increase is 17.25. while the increase in the average value of student skills in cycle I was an increase of II from the analysis above, it can be understood that the use of the STAD type cooperative learning model can improve student learning result on theme 7, theme 8 and theme 9 in class V.